Pollination of Anthurium (Araceae) by derelomine flower weevils (Coleoptera: Curculionidae) - M. Franz, Nico (2007)
Cyclanthura flower weevils (Coleoptera: Curculionidae: Derelomini) are identified for the first time as pollinators of multiple species of Anthurium (Araceae) in Costa Rica. The weevils are present on the inflorescences in small numbers during the pistillate and staminate phase of anthesis, and consume plant tissues and pollen. The individuals of one species of Cyclanthura can visit several Anthurium species within the same locality. They also engage in reproductive activities and are likely to oviposit into the flowers. The mating strategies suggest that sperm precedence selects males that are able to secure their position as the last partner prior to oviposition.